Beowulf, the Icelander. A comparative Study between the Poem and the Nordic Tradition - Oliveros García, Jaime (Journal of Artistic Creation and Literary Research, 2025)
This article examines the main roots of the epic poem Beowulf and suggests the possibility of its belonging more to the Nordic/Germanic tradition rather than any other. As it will be shown, this poem nourishes itself with elements that are extremely similar to those used by Skaldic poets and Old Nordic Storytellers. To make the relation clearer between these two traditions, the article focuses on five different issues: the first one deals with the historical background when Beowulf might have been written, roughly the tenth or eleventh century. Then, the essay focuses on a comparison between Old English and Old Nordic poetry in order to see the structural interrelation between them. The following part deals with content, comparing the poem to what is probably the most important Icelandic narrative corpus. By comparing Beowulf with Icelandic sögur, the paper does not attempt to relate such enormous literary works. The intention is to compare the main issues dealt with in the texts. After analyzing the poem as a whole -structure and content-, the discussion swifts in order to show the cultural issues that are of importance in understanding the correlation between these texts, approaching them in the tradition of Proppian Folk-tale structure, and thus dealing with Indo-European arguments that arguably state the origin of these narratives.